High-strength, high-toughness and low-heat-generation dual-bonded graphene / natural rubber based on high-molecular-weight cationic polymer and simplified preparation

The graphene oxide is positively modified through high molecular weight cationic polymers and forms bonds with natural latex particles. The bonded particles participate in the crosslinking reaction of the rubber molecular chain during the vulcanization stage, which solves the problem that graphene oxide is difficult to disperse evenly in natural rubber, and improves the strength, toughness and low thermal properties of the composite material.

CN119684688AInactive Publication Date: 2025-03-25ZHONGBEI UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411856325.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Graphene oxide (GO) is difficult to disperse uniformly in natural rubber (NR) matrix, resulting in weak interface interactions and affecting the performance of rubber composite materials.

Method used

By positively modifying graphene oxide using high molecular weight cationic polymers and bonding it with negatively charged natural latex particles, bonding particles of positively charged graphene oxide and negatively charged natural latex particles are formed. Subsequently, during the vulcanization stage, the hydrophobic portion of the high-molecular-weight cationic polymer participates in the cross-linking reaction of the rubber molecular chain, forming chemical bond connections, and improving interface interactions.

Benefits of technology

The uniform dispersion and strengthening interface interaction of graphene oxide in natural rubber are achieved, and the strength, toughness and low thermal performance of composite materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684688A_ABST
    Figure CN119684688A_ABST
Patent Text Reader

Abstract

The invention relates to the field of graphene and functional rubber composite materials thereof, in particular to high-strength, high-toughness and low-heat-generation dual-bonded graphene / natural rubber based on a high-molecular-weight cationic polymer and simplified preparation of the high-strength, high-toughness and low-heat-generation dual-bonded graphene / natural rubber based on the high-molecular-weight cationic polymer. The positively charged high molecular weight cationic polymer modified graphene oxide particles and the negatively charged natural latex particles can form a bonding effect; a hydrophobic part of the high molecular weight cationic polymer participates in a cross-linking reaction of a rubber molecular chain in a natural rubber vulcanization stage, so that the high molecular weight cationic polymer modified graphene oxide and a natural rubber matrix form chemical bonding connection; finally, the high-strength, high-toughness and low-heat-generation dual-bonded graphene / natural rubber based on the high-molecular-weight cationic polymer is obtained. The tensile strength, tear strength, dynamic compression heat generation and wear resistance of the modified natural rubber are all remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of graphene and functional rubber composite materials thereof, and in particular to a high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on a high-molecular-weight cationic polymer and a simplified preparation method thereof. Background Art

[0002] Natural rubber (NR) latex is a renewable polymer material obtained from rubber trees, containing a milky white colloidal material, cis-1,4-polyisoprene. Adding a compounding agent in the form of a water dispersion to the latex makes a batch latex, which is then gelled under the action of a coagulant. The wet gel is leached, dried, and vulcanized to obtain the NR product.

[0003] NR has excellent mechanical properties, tear resistance, elasticity, etc., and is widely used in automobile tires, wires, cables and other fields. However, NR needs to add fillers to achieve its multiple functions, including high modulus, high tear resistance and high thermal conductivity. In addition, in order to manufacture rubber composites with excellent comprehensive properties, nanoparticles with small size and large surface area have become an ideal choice for rubber matrix reinforcing fillers, among which the representative ones are mainly nano carbon black, carbon nanotubes, nano montmorillonite, graphene, etc.

[0004] Graphene oxide (GO) is a two-dimensional (2D) material with multiple oxygen-containing functional groups obtained by oxidizing graphite through physical and chemical means. It is an economical way to mass produce graphene. Graphene and its derivatives have excellent mechanical strength, electrical conductivity and thermal conductivity, and are widely used to enhance and modify rubber to make the prepared rubber composites have better mechanical strength, toughness and thermal conductivity.

[0005] High molecular weight cationic polymers are linear biocompatible polymers with positive charges on the macromolecular chain, usually polymerized from monomers containing cationic groups such as amino groups and quaternary ammonium salts. These cationic groups enable the polymer to ionize cations in systems such as solutions, and are reported to be able to insert into GO sheets, reducing the number of GO layers. High molecular weight cationic polymers have shown extraordinary charm in the field of materials science due to their unique properties, such as near-zero vapor pressure, strong polarity, excellent thermal stability, and large electrochemical window, and have attracted widespread attention from researchers and related industries around the world. In recent years, with the continuous development of material modification technology, high molecular weight cationic polymers have shined in the field of filler modification with their own advantages, and have been widely used in filler modification, opening up new ways to improve material performance.

[0006] The performance of nanofiller modified rubber composites is affected by two major factors, one is the dispersibility of the filler, and the other is the interface interaction between the filler and the rubber matrix. The interface interaction between the nanofiller and the polymer matrix is ​​the main factor leading to changes in rubber properties and has an important influence on the dispersion of the nanofiller. When only van der Waals forces or hydrogen bonds exist, the layers of GO are easily agglomerated together, which not only makes it difficult for GO to be evenly dispersed in the NR matrix, but also leads to problems such as weak bonding between the two phases, resulting in unsatisfactory modification of NR. Therefore, it is urgent to develop a new type of rubber composite material and its preparation technology that can build a strong interface bonding force between GO and NR, so as to not only improve the stability and durability of rubber products, but also optimize other properties at the same time. Summary of the invention

[0007] In order to solve the problem that GO is difficult to be evenly dispersed in a NR matrix, the present invention provides a high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on a high molecular weight cationic polymer and a simplified preparation method.

[0008] The invention is realized by the following technical scheme: a high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on a high-molecular-weight cationic polymer, wherein the hydrophilic part of the high-molecular-weight cationic polymer ionizes cations in water, so that the high-molecular-weight cationic polymer-modified graphene oxide particles in the water phase are positively charged, and the proteins and lipids adsorbed on the surface of the natural latex particles make them negatively charged; when the high-molecular-weight cationic polymer-modified graphene oxide aqueous dispersion is added to the natural latex, the positively charged high-molecular-weight cationic polymer-modified graphene oxide particles and the negatively charged natural latex particles form a bonding reaction; the hydrophobic part of the high-molecular-weight cationic polymer participates in the cross-linking reaction of the rubber molecular chain in the natural rubber vulcanization stage, so that the high-molecular-weight cationic polymer-modified graphene oxide forms a chemical bonding connection with the natural rubber matrix; finally, the high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on the high-molecular-weight cationic polymer is obtained.

[0009] As a further improvement of the technical solution of the present invention, the high molecular weight cationic polymer is a high molecular weight cationic polymer containing double bonds, and the molecular weight is 40,000 to 100,000.

[0010] As a further improvement of the technical solution of the present invention, the high molecular weight cationic polymer containing double bonds is selected from at least one of polydiallyldimethylammonium chloride, polyethyleneimine, polyacrylamide and polyallylamine hydrochloride or a mixture of two or more thereof.

[0011] The present invention further provides a simplified preparation process of high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer, comprising the following steps:

[0012] ① Dispersing a high molecular weight cationic polymer in water, treating it at an ultrasonic power of S1 for a time of t1, adding a graphene oxide aqueous dispersion, treating it at an ultrasonic power of S2 for a time of t2, and reacting it at a temperature of T1 under magnetic stirring for a time of t3 to obtain a high molecular weight cationic polymer modified graphene oxide aqueous dispersion;

[0013] ② Prepare a natural rubber latex water dispersion system, then add the high molecular weight cationic polymer modified graphene oxide water dispersion prepared in step ① and mix them evenly. During this process, the positively charged high molecular weight cationic polymer modified graphene oxide particles and the negatively charged natural rubber latex particles will form combined particles through bonding; add a flocculant to flocculate, wash the obtained raw rubber with water, dehydrate, and dry it to obtain a high molecular weight cationic polymer modified graphene oxide / natural rubber masterbatch;

[0014] ③ The high molecular weight cationic polymer modified graphene oxide / natural rubber masterbatch obtained in step ② is mixed and an antioxidant, an antioxidant, an activator, a softener, a vulcanization accelerator and a reinforcing filler are added in sequence to obtain a mixed rubber after being evenly dispersed; the mixed rubber is mixed and a vulcanizing agent is added, and after being evenly mixed, it is thinly passed until there are no bubbles in the rubber material, and after being parked for a time t4, it is placed in a mold for vulcanization. During the vulcanization process, the double bonds in the hydrophobic part of the high molecular weight cationic polymer participate in the cross-linking reaction of the natural rubber molecular chain, so that the high molecular weight cationic polymer modified graphene oxide and the natural rubber matrix are chemically bonded, and finally a high-strength, high-toughness and low-heat-generation double-bonded graphene / natural rubber based on the high molecular weight cationic polymer is obtained.

[0015] As a further improvement of the streamlined preparation process technical scheme of the present invention, in step ①, the concentration of the prepared high molecular weight cationic polymer solution is 0.5-5 mg / mL, the ultrasonic power S1 is 50-250 W, and the time t1 is 5-25 min; the concentration of the added graphene oxide aqueous dispersion is 0.5-5 mg / mL, the mass ratio of the high molecular weight cationic polymer to graphene oxide is 3-9:10, the ultrasonic power S2 is 50-250 W, the time t2 is 5-25 min, the temperature T1 is 20-80 ° C, and the time t3 is 2-6 h.

[0016] As a further improvement of the simplified preparation process technical solution of the present invention, in step ②, the concentration of the natural rubber latex aqueous dispersion system is prepared to be 10 to 40 wt%.

[0017] As a further improvement of the streamlined preparation process technical scheme of the present invention, in step ③, 100 parts by mass of natural rubber, 0.1 to 2 parts by mass of high molecular weight cationic polymer modified graphene oxide particles, 30 to 90 parts by mass of reinforcing filler, and 10 to 20 parts by mass of rubber additives are used.

[0018] As a further improvement of the simplified preparation process technical solution of the present invention, in step ③, the mass ratio of the vulcanization accelerator: antioxidant: anti-aging agent: activator: softener: vulcanizing agent is 2:2:2:5:2:2.

[0019] As a further improvement of the streamlined preparation process technical scheme of the present invention, in step ③, the vulcanization accelerator is N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide or N-(diethylene oxide)-2-benzothiazole sulfenamide; the antioxidant is N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, p-phenylaniline or dilauryl dipropionate sulfide; the antioxidant is 2,6-di-tert-butyl-4-methylphenol, 2,2,4-trimethyl-1,2-dihydroquinoline polymer or 2-thiol benzoimidazole; the activator is zinc gluconate, zinc oxide or magnesium oxide; the softener is stearic acid, dibutyl titanate or dioctyl adipate; the reinforcing filler is carbon black, silica or clay; and the vulcanizing agent is sulfur or sulfur monochloride.

[0020] As a further improvement of the streamlined preparation process technical scheme of the present invention, in step ③, the banburying temperature is 105-120°C, and the banburying time is 9-15min; the open mixing temperature is 50-70°C, and the open mixing time is 8-12min; the parking time t4 is 18-36h; the vulcanization temperature T2 is 135-170°C, the vulcanization pressure is 10-30MPa, and the vulcanization time t5 is 3-25min.

[0021] The high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer and simplified preparation provided by the present invention have the following advantages compared with the prior art:

[0022] (1) The present invention utilizes a simplified process that is easy to industrialize to positively charge graphene oxide with a high molecular weight cationic polymer, while the proteins and lipids adsorbed on the surface of natural latex particles make them negatively charged. When an aqueous dispersion of graphene oxide modified with a high molecular weight cationic polymer is added to natural latex, the positively charged high molecular weight cationic polymer modified graphene oxide particles and the negatively charged natural latex particles form a bonding reaction, which, on the one hand, helps the high molecular weight cationic polymer modified graphene oxide to be uniformly dispersed in natural rubber, and on the other hand, can enhance the interfacial interaction between the natural rubber matrix and the modified graphene.

[0023] (2) The hydrophobic end of the high molecular weight cationic polymer of the present invention is a long chain structure with double bonds. During the vulcanization stage, it can participate in the cross-linking reaction of the rubber molecular chain, so that the high molecular weight cationic polymer modified graphene oxide and the natural rubber matrix form a chemical bond connection, thereby limiting the movement of the natural rubber molecular chain and making the natural rubber molecular chain more densely distributed in space, thereby increasing the cross-linking density of the natural rubber vulcanizate and making the cross-linking network more perfect, reducing the frictional heat generated between the filler-matrix and between the filler-filler, and finally obtaining a graphene-modified natural rubber composite material with high strength, high toughness and low heat generation.

[0024] (3) The present invention uses modified graphene oxide aqueous dispersion and natural rubber latex as raw materials, and adopts an aqueous phase synergistic coagulation process that is efficient, energy-saving, and environmentally friendly. Conventional equipment is involved and there are no stringent requirements. Therefore, it is easy to industrialize production and helps to promote the tire industry towards a more environmentally friendly and high-performance direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0027] Figure 1 Example 2 High molecular weight cationic polymer polydiallyldimethylammonium chloride (PDDA) modified GO (characterized as PDDA@GO, abbreviated as PGO) + ) aqueous dispersion and its modified natural rubber latex (characterized as NR / PDDA@GO, abbreviated as NR / PGO + )'s Zeta potential.

[0028] Figure 2 XRD spectrum of PDDA@GO prepared in Example 2.

[0029] Figure 3 DSC curves of GO-modified NR composites prepared in Examples 1-3 and Comparative Example 1.

[0030] Figure 4 Crosslinking density of GO-modified NR composites prepared in Examples 1-3 and Comparative Example 1.

[0031] Figure 5 Binder content of GO-modified NR composites prepared in Examples 1-3 and Comparative Example 1.

[0032] The test method of the above-mentioned figure is:

[0033] Zeta potential test: A test solution with a concentration of 0.25 mg / mL was prepared and measured three times using a Zeta potential analyzer (Malvern, UK) to obtain the average value.

[0034] X-ray diffraction analysis (XRD): using Cu target material, Kα rays (λ=0.1546 nm) were continuously scanned on the sample at a speed of 5° / min in the range of 5-80°.

[0035] DSC test: nitrogen atmosphere, heating rate 5℃ / min, cooling rate 5℃ / min, test range -80℃~25℃.

[0036] Determination of crosslink density of vulcanized rubber: Weigh 0.5g of vulcanized rubber, recorded as m0, and soak it in an appropriate amount of toluene. Replace the toluene every 24 hours. After 72 hours, take out the swollen material and place it on filter paper; after the surface toluene is completely removed, weigh it and record it as m1; then, dry it at 50°C to constant weight, weigh it and record it as m2. The crosslink density is calculated using the following formula:

[0037]

[0038] Where: V r is the volume fraction of rubber in the equilibrium swelling, φ is the mass fraction of rubber in the sample, α is the mass loss rate of the sample during the swelling process, and ρ r is the density of the rubber composite, ρ s is the density of the solvent toluene.

[0039] The crosslink density was calculated according to the Flory-Rehner formula:

[0040]

[0041] Where: Ve is the crosslinking density of the rubber, V s is the molar volume of the solvent toluene, and χ is the solvent interaction parameter between rubber and toluene.

[0042] Determination of the binder content of the mixed rubber: The binder content was tested using a differential scanning calorimeter. The test was carried out at a temperature of -80 to 25°C and a heating rate of 5°C / min. The binder content was calculated using the following formula:

[0043] ΔC pn =ΔC p / (1-w)

[0044] χ im =(ΔC p0 -ΔCpn ) / ΔC p0

[0045] from Figure 1 The Zeta diagram in Figure 2 shows that the GO aqueous dispersion itself is negatively charged. After being modified by a high molecular weight cationic polymer, a positively charged GO (i.e., PGO) was successfully obtained. + ). In addition, compared with GO-modified natural rubber latex, PGO + The potential of the modified natural rubber latex becomes larger because the positively charged PGO + The PGO forms a bond with the negatively charged natural rubber particles in the latex, resulting in + The potential of the modified natural rubber latex becomes larger.

[0046] Depend on Figure 2 It can be seen that the (001) diffraction peak of pure GO at 2θ = 12.11° is + The spectrum of GO shifts to the left to 8.66°. According to the Bragg equation, the interlayer spacing of GO is 0.74nm, while that of PGO is + The interlayer spacing is as high as 1.03 nm, and the significant increase in the interlayer spacing indicates that GO has been successfully modified.

[0047] The DSC curves can be used to determine the interaction between the NR matrix and the modified GO filler, since the presence of the filler usually causes a shift in the glass transition temperature of the rubber matrix. Figure 3 From the DSC curves, it can be seen that the glass transition temperatures of the NR composite materials prepared in Examples 1-3 are all increased compared with Comparative Example 1. The reason is that the hydrophilic end quaternary ammonium cations of PDDA in the aqueous phase make the modified graphene oxide particles positively charged, while the proteins and lipids adsorbed on the surface of the natural latex particles make them negatively charged. When the high molecular weight cationic polymer modified graphene oxide aqueous dispersion is added to the natural latex, the positively charged high molecular weight cationic polymer modified graphene oxide particles and the negatively charged natural latex particles will form a bonding reaction, which on the one hand helps the high molecular weight cationic polymer modified graphene oxide to be uniformly dispersed in the natural rubber, and on the other hand can improve the interfacial interaction between the natural rubber matrix and the modified graphene.

[0048] Figure 4The cross-linking density of the prepared graphene-modified natural rubber composite material is shown. Compared with Comparative Example 1, the cross-linking density of the natural rubber vulcanizates prepared in Examples 1-3 is significantly improved, and with the increase of the content of high molecular weight cationic polymer, the cross-linking density increases, and the cross-linking network is more perfect. The reason is that the molecular structure of PDDA itself can promote chemical cross-linking to a certain extent. The hydrophobic end of PDDA is a long chain structure with a double bond. In the vulcanization stage, it can participate in the cross-linking reaction of the NR molecular chain, so that the PDDA-modified GO and the NR matrix form a chemical bond connection, thereby limiting the movement of the NR molecular chain, and making the NR molecular chain more closely distributed in space, thereby increasing the cross-linking density of the NR vulcanizate and making the cross-linking network more perfect, reducing the friction heat between the filler-matrix and the filler-filler, and finally obtaining a high-strength, high-toughness and low-heat graphene-modified natural rubber composite material.

[0049] The formation of the cross-linked network structure depends largely on the bound rubber content, which in turn depends on the interaction between the matrix and filler in the composite rubber. Figure 5 The graphene-modified natural rubber composite material has a binder content. It can be seen that compared with the comparative example 1, the binder content of the composite materials prepared in Examples 1-3 is significantly increased, and the binder content increases with the increase of the high molecular weight cationic polymer content. The reason is that the positively charged PGO + The bonding effect between the negatively charged natural rubber particles in the latex and the chemical bonding effect between the PDDA-modified GO and the NR matrix formed by the long double-bond structure at the hydrophobic end of PDDA participating in the NR cross-linking reaction will double enhance the interfacial bonding strength between the NR matrix and GO. DETAILED DESCRIPTION

[0050] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0051] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0052] The invention provides a specific embodiment of high-strength, high-toughness and low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymers. The hydrophilic part of the high molecular weight cationic polymer ionizes cations in water, so that the high molecular weight cationic polymer-modified graphene oxide particles in the water phase are positively charged, and the proteins and lipids adsorbed on the surface of the natural latex particles make them negatively charged; when the high molecular weight cationic polymer-modified graphene oxide aqueous dispersion is added to the natural latex, the positively charged high molecular weight cationic polymer-modified graphene oxide particles and the negatively charged natural latex particles form a bonding reaction; the hydrophobic part of the high molecular weight cationic polymer participates in the cross-linking reaction of the rubber molecular chain in the vulcanization stage of the natural rubber, so that the high molecular weight cationic polymer-modified graphene oxide forms a chemical bonding connection with the natural rubber matrix; finally, the high-strength, high-toughness and low-heat-generation double-bonded graphene / natural rubber based on the high molecular weight cationic polymer is obtained.

[0053] In one embodiment provided by the present invention, the high molecular weight cationic polymer is a high molecular weight cationic polymer containing double bonds, and the molecular weight is 40,000-100,000.

[0054] In another embodiment provided by the present invention, the high molecular weight cationic polymer containing double bonds is selected from at least one of polydiallyldimethylammonium chloride, polyethyleneimine, polyacrylamide and polyallylamine hydrochloride or a mixture of two or more thereof.

[0055] The present invention also provides a simplified preparation process of the high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on a high molecular weight cationic polymer, comprising the following steps:

[0056] ① Dispersing a high molecular weight cationic polymer in water, treating it at an ultrasonic power of S1 for a time of t1, adding a graphene oxide aqueous dispersion, treating it at an ultrasonic power of S2 for a time of t2, and reacting it at a temperature of T1 under magnetic stirring for a time of t3 to obtain a high molecular weight cationic polymer modified graphene oxide aqueous dispersion;

[0057] ② Prepare a natural rubber latex water dispersion system, then add the high molecular weight cationic polymer modified graphene oxide water dispersion prepared in step ① and mix them evenly. During this process, the positively charged high molecular weight cationic polymer modified graphene oxide particles and the negatively charged natural rubber latex particles will form combined particles through bonding; add a flocculant to flocculate, wash the obtained raw rubber with water, dehydrate, and dry it to obtain a high molecular weight cationic polymer modified graphene oxide / natural rubber masterbatch;

[0058] ③ The high molecular weight cationic polymer modified graphene oxide / natural rubber masterbatch obtained in step ② is mixed and an antioxidant, an antioxidant, an activator, a softener, a vulcanization accelerator and a reinforcing filler are added in sequence to obtain a mixed rubber after being evenly dispersed; the mixed rubber is mixed and a vulcanizing agent is added, and after being evenly mixed, it is thinly passed until there are no bubbles in the rubber material, and after being parked for a time t4, it is placed in a mold for vulcanization. During the vulcanization process, the double bonds in the hydrophobic part of the high molecular weight cationic polymer participate in the cross-linking reaction of the natural rubber molecular chain, so that the high molecular weight cationic polymer modified graphene oxide and the natural rubber matrix are chemically bonded, and finally a high-strength, high-toughness, low-yield double-bonded thermal graphene / natural rubber based on the high molecular weight cationic polymer is obtained.

[0059] In one embodiment of the present invention, in step ①, the concentration of the prepared high molecular weight cationic polymer solution is 0.5-5 mg / mL, the ultrasonic power S1 is 50-250 W, and the time t1 is 5-25 min; the concentration of the added graphene oxide aqueous dispersion is 0.5-5 mg / mL, the mass ratio of the high molecular weight cationic polymer to graphene oxide is 3-9:10, the ultrasonic power S2 is 50-250 W, the time t2 is 5-25 min, the temperature T1 is 20-80 ° C, and the time t3 is 2-6 h.

[0060] In another embodiment of the present invention, in step ②, the concentration of the natural rubber latex aqueous dispersion system is prepared to be 10-40wt%.

[0061] In one embodiment of the present invention, in step ③, 100 parts by mass of natural rubber, 0.1 to 2 parts by mass of high molecular weight cationic polymer modified graphene oxide particles, 30 to 90 parts by mass of reinforcing filler, and 10 to 20 parts by mass of rubber additives are used.

[0062] In another embodiment of the present invention, in step ③, the mass ratio of the vulcanization accelerator: antioxidant: anti-aging agent: activator: softener: vulcanizing agent is 2:2:2:5:2:2.

[0063] In one embodiment of the present invention, in step ③, the vulcanization accelerator is N-tert-butyl-2-benzothiazole sulfenamide, N-cyclohexyl-2-benzothiazole sulfenamide or N-(diethylene oxide)-2-benzothiazole sulfenamide; the antioxidant is N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, p-phenylaniline or dilauryl dipropionate sulfide; the antioxidant is 2,6-di-tert-butyl-4-methylphenol, 2,2,4-trimethyl-1,2-dihydroquinoline polymer or 2-thiol benzoimidazole; the activator is zinc gluconate, zinc oxide or magnesium oxide; the softener is stearic acid, dibutyl titanate or dioctyl adipate; the reinforcing filler is carbon black, silica or clay; and the vulcanizing agent is sulfur or sulfur monochloride.

[0064] In another embodiment of the present invention, in step ③, the banburying temperature is 105-120°C, and the banburying time is 9-15min; the open mixing temperature is 50-70°C, and the open mixing time is 8-12min; the parking time t4 is 18-36h; the vulcanization temperature T2 is 135-170°C, the vulcanization pressure is 10-30MPa, and the vulcanization time t5 is 3-25min.

[0065] The specific embodiments of the present invention are described in detail below.

[0066] Embodiment 1:

[0067] A simplified preparation process of high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer PDDA, comprising the following steps:

[0068] ① Disperse 0.25phr (1g per phr) PDDA in 125mL water, ultrasonic power 200W, ultrasonic time 10min, then add GO aqueous dispersion with a concentration of 2mg / mL, the mass ratio of PDDA to GO is 5:10, ultrasonic power 200W, ultrasonic time 15min, react under magnetic stirring at 25℃ for 2h to obtain PDDA-modified GO aqueous dispersion.

[0069] ② Add a certain amount of deionized water to natural rubber latex and disperse it evenly to obtain a natural rubber latex with a concentration of 30wt%, then add the PDDA-modified GO aqueous dispersion prepared in step ① and mix evenly. During this process, the hydrophilic end of PDDA ionizes quaternary ammonium cations, making the PDDA-modified GO particles positively charged, and the proteins and lipids adsorbed on the surface of the natural rubber latex particles make them negatively charged. Therefore, when the PDDA-modified GO aqueous dispersion is added to natural rubber latex, the two will form combined particles through bonding; add 10wt% CaCl2 solution flocculant for flocculation, wash the obtained raw rubber with water, dehydrate it and dry it at 60°C to constant weight to obtain PDDA-modified GO / NR masterbatch.

[0070] ③ The PDDA-modified GO / NR masterbatch containing 100 phr of natural rubber obtained in step ② was placed in an internal mixer and mixed at 110°C. During the mixing, 2 phr of vulcanization accelerator N-cyclohexyl-2-benzothiazole sulfonamide, 2 phr of antioxidant N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, 2 phr of antioxidant 2,6-di-tert-butyl-4-methylphenol, 5 phr of activator zinc oxide, 2 phr of softener stearic acid and 35 phr of reinforcing filler carbon black were added three times. The mixture was mixed for 12 minutes and the rubber was discharged. After the rubber was cooled to room temperature, it was transferred to an open mixer and mixed at 60°C. 2 phr of sulfur was added and mixed evenly. After mixing, the mixture was thinly passed until there were no bubbles in the rubber for a total of 10 minutes. After 24 hours of mixing, the mixed rubber sheet was placed in a mold and vulcanized at 150°C and 15 MPa for a certain time (t c90 )(6min;t c90 Measured by the rubber processing analyzer (RPA), during the vulcanization process, the double bond at the hydrophobic end of PDDA will participate in the cross-linking reaction of the NR molecular chain, so that the PDDA-modified GO forms a chemical bond with the NR matrix, and finally a double-bonded natural rubber composite material with high strength, high toughness and low heat generation is obtained.

[0071] Embodiment 2:

[0072] The preparation process is exactly the same as that in Example 1, except that the amount of PDDA added in step ① is 0.35 phr, that is, the mass ratio of PDDA to GO is 7:10.

[0073] Embodiment 3:

[0074] The preparation process is exactly the same as that in Example 1, except that the amount of PDDA added in step ① is 0.45 phr, that is, the mass ratio of PDDA to GO is 9:10.

[0075] The formulas of Examples 1-3 are shown in Table 1, and the performance test results are shown in Table 2.

[0076] Comparative Example 1:

[0077] A simplified preparation process of a GO-modified NR composite material comprises the following steps:

[0078] ① Add deionized water to GO and disperse it evenly to obtain a GO aqueous dispersion with a concentration of 2 mg / mL.

[0079] ② The same as step ② of Examples 1 to 3, except that the PDDA-modified GO in step ② of Examples 1 to 3 is replaced with GO of equal mass.

[0080] ③ The same as step ③ of Examples 1 to 3. The formula of Comparative Example 1 is shown in Table 1, and the performance test results are shown in Table 2.

[0081] The natural rubber composite materials obtained in Examples 1-3 and Comparative Example 1 were subjected to performance tests. The test standard for tensile properties was ISO 37-2005, and the tensile rate was 500 mm / min. The test standard for tear properties was GB / T529-2008. The test standard for hardness was GB / T 531.1-2008. The test standard for heat generation properties was GB / T1687.1-2016. The test standard for abrasion properties was GB / T 9867-2008.

[0082] Table 1 Formula table of Examples 1 to 3 and Comparative Example 1

[0083]

[0084] Table 2 Performance test results of natural rubber composite materials prepared in Examples 1 to 3 and Comparative Example 1

[0085]

[0086]

[0087] As can be seen from Table 2, the tensile strength, tear strength, dynamic compression heat generation and wear resistance of the high-strength, high-toughness and low-heat generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer of the present invention are significantly improved compared with the GO-modified NR composite material of Comparative Example 1, achieving high strength, high toughness and low heat generation of natural rubber.

[0088] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.

Claims

1. A high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on a high molecular weight cationic polymer, characterized in that: The hydrophilic part of the high molecular weight cationic polymer ionizes cations in water, so that the high molecular weight cationic polymer modified graphene oxide particles in the water phase are positively charged, and the proteins and lipids adsorbed on the surface of the natural latex particles make them negatively charged; when the high molecular weight cationic polymer modified graphene oxide aqueous dispersion is added to the natural latex, the positively charged high molecular weight cationic polymer modified graphene oxide particles and the negatively charged natural latex particles will form a bonding effect; the hydrophobic part of the high molecular weight cationic polymer participates in the cross-linking reaction of the rubber molecular chain during the vulcanization stage of the natural rubber, so that the high molecular weight cationic polymer modified graphene oxide forms a chemical bonding connection with the natural rubber matrix; finally, a high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on the high molecular weight cationic polymer is obtained.

2. A high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on a high molecular weight cationic polymer according to claim 1, characterized in that: The high molecular weight cationic polymer is a high molecular weight cationic polymer containing double bonds, and the molecular weight is 40,000-100,000.

3. A high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer according to claim 2, characterized in that: The high molecular weight cationic polymer containing double bonds is selected from at least one of polydiallyldimethylammonium chloride, polyethyleneimine, polyacrylamide and polyallylamine hydrochloride or a mixture of two or more thereof.

4. A streamlined preparation process for high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymers as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: ① Dispersing a high molecular weight cationic polymer in water, treating it at an ultrasonic power of S1 for a time of t1, adding a graphene oxide aqueous dispersion, treating it at an ultrasonic power of S2 for a time of t2, and reacting it at a temperature of T1 under magnetic stirring for a time of t3 to obtain a high molecular weight cationic polymer modified graphene oxide aqueous dispersion; ② Prepare a natural rubber latex water dispersion system, then add the high molecular weight cationic polymer modified graphene oxide water dispersion prepared in step ① and mix them evenly. During this process, the positively charged high molecular weight cationic polymer modified graphene oxide particles and the negatively charged natural rubber latex particles will form combined particles through bonding. Add a flocculant for flocculation, wash the obtained raw rubber with water, remove water, and dry it to obtain a high molecular weight cationic polymer modified graphene oxide / natural rubber masterbatch; ③ The high molecular weight cationic polymer modified graphene oxide / natural rubber masterbatch obtained in step ② is mixed and a vulcanization accelerator, an antioxidant, an anti-aging agent, an activator, a softener and a reinforcing filler are added in sequence to obtain a mixed rubber after being evenly dispersed; the mixed rubber is mixed and a vulcanizer is added to the mixed rubber, and after being evenly mixed, it is thinly passed until there are no bubbles in the rubber material, and after being parked for a time t4, it is placed in a mold for vulcanization. During the vulcanization process, the double bonds in the hydrophobic part of the high molecular weight cationic polymer participate in the cross-linking reaction of the natural rubber molecular chain, so that the high molecular weight cationic polymer modified graphene oxide and the natural rubber matrix are chemically bonded, and finally a high-strength, high-toughness and low-heat-generation double-bonded graphene / natural rubber based on the high molecular weight cationic polymer is obtained.

5. A streamlined preparation process for high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer according to claim 4, characterized in that: In step ①, the concentration of the prepared high molecular weight cationic polymer solution is 0.5-5 mg / mL, the ultrasonic power S1 is 50-250 W, and the time t1 is 5-25 min; the concentration of the added graphene oxide aqueous dispersion is 0.5-5 mg / mL, the mass ratio of the high molecular weight cationic polymer to graphene oxide is 3-9:10, the ultrasonic power S2 is 50-250 W, the time t2 is 5-25 min, the temperature T1 is 20-80 °C, and the time t3 is 2-6h.

6. A streamlined preparation process for high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer according to claim 4, characterized in that: In step ②, the concentration of the natural rubber latex aqueous dispersion system is prepared to be 10 to 40 wt%.

7. A streamlined preparation process for high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer according to claim 4, characterized in that: In step ③, 100 parts by mass of natural rubber, 0.1 to 2 parts by mass of high molecular weight cationic polymer modified graphene oxide particles, 30 to 90 parts by mass of reinforcing filler, and 10 to 20 parts by mass of rubber additives are added.

8. A streamlined preparation process for high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer according to claim 4, characterized in that: In step ③, the mass ratio of the vulcanization accelerator: antioxidant: anti-aging agent: activator: softener: vulcanizing agent is 2:2:2:5:2:

2.

9. A streamlined preparation process for high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer according to claim 4, characterized in that: In step ③, the vulcanization accelerator is N-tert-butyl-2-benzothiazole sulfonamide, N-cyclohexyl-2-benzothiazole sulfonamide or N-(diethylene oxide)-2-benzothiazole sulfonamide; the antioxidant is N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, p-phenylaniline or dilauryl dipropionate sulfide; the antioxidant is 2,6-di-tert-butyl-4-methylphenol, 2,2,4-trimethyl-1,2-dihydroquinoline polymer or 2-thiol benzoimidazole; the activator is zinc gluconate, zinc oxide or magnesium oxide; the softener is stearic acid, dibutyl titanate or dioctyl adipate; the reinforcing filler is carbon black, silica or clay; and the vulcanizing agent is sulfur or sulfur monochloride.

10. A streamlined preparation process for high-strength, high-toughness, low-heat-generation double-bonded graphene / natural rubber based on high molecular weight cationic polymer according to claim 4, characterized in that: In step ③, the banburying temperature is 105-120 ° C, the banburying time is 9-15 min; the open mixing temperature is 50-70 ° C, the open mixing time is 8-12 min; the parking time t4 is 18-36 h; the vulcanization temperature T2 is 135-170 ° C, the vulcanization pressure is 10-30 MPa, and the vulcanization time t5 is 3-25 min.

Citation Information

Patent Citations

  • Functional modified graphene as well as preparation method and application thereof

    CN107298438A

  • Preparation method of polymer modified graphene composite material

    CN108530699A

  • Water-phase synergistic coagulation process production line and production process of graphene oxide modified natural rubber master batch

    CN118878720A

  • Graphene composite and method for preparing the same

    KR1020150076632A